Reporting Application of Groundwater Use Volume by Industrial Taxpayers: Case Study on One of The Services in Bandung District - Ananta, Wulan Avisenia; Sudrajat, Asep; Dianto, Aris; Fahmi, Miftah; Damayanti, Resti Aulia (LPPM STMIK Mardira Indonesia, 2023)
The Bandung District's Regional Revenue Agency (BAPENDA), primarily tasked with managing local taxes, currently utilizes computer technology for most of its operations, albeit not to its full potential. Currently, manual techniques that utilize paper are still utilized to report the amount of groundwater consumption by taxpayers. As a result, this can affect the accurate computation of groundwater taxes and lead to delays in distributing information regarding groundwater taxes. This study aims to develop an application that enables taxpayers to report the amount of groundwater they use efficiently. This application will also facilitate the access of groundwater usage reports by Tax Division I, hence enhancing convenience. The Final Project utilizes a descriptive research methodology, whereas the system development process employs OOAD (Object-Oriented Analysis and Design). This application system is designed using the PHP programming language and utilizes the MySQL XAMPP database. The chosen framework is CodeIgniter due to its extensive range of capabilities that facilitate the creation of robust and high-performing web applications. To summarize, this research has effectively developed an application that allows taxpayers in the Bapenda of Bandung District to submit their groundwater usage volume. This application simplifies the reporting procedure for taxpayers and assists Tax Division I in accessing groundwater usage statistics.